Evaluation of Information Technology Service Governance Using the ITIL Method : A Strategy for Improving Business Intelligence Efficiency at Bank Rakyat Indonesia - Andysah Putera Utama Siahaan; Wiko Pratama; Juliyandri Saragih; Muhammad Indra; Muhammad Wahyudi (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Information Technology (IT) service management plays a critical role in supporting the efficiency and effectiveness of business intelligence processes within modern organizations. This study aims to evaluate IT service governance in Bank Rakyat Indonesia using the Information Technology Infrastructure Library (ITIL) framework. This approach focuses on improving operational efficiency, service management, and aligning IT services with business needs. The research method involves a detailed analysis of service processes and activities based on ITIL stages, ranging from service strategy to continuous improvement. The findings indicate that ITIL implementation significantly enhances IT service management and promotes business intelligence effectiveness within the organization. Recommendations for further development are also provided to improve the quality and speed of IT services in the future.